Memórias manchadas e ruínas memoriais em A mancha e “O condomínio”, de Luis Fernando Veríssimo - Leila Lehnen (Estudos de Literatura Brasileira Contemporânea)
This article proposes that what it calls “schizophrenic memory sites” – places that are constructed as palimpsests of various (and, at times, contradictory) versions of the past – are connected with what anthropologist James Hoslton (2008) denominates “differentiated citizenship”. The article establishes an analogy between differentiated memory rights and the constitutional measures that legalize social and civil differences and that, according to Holston, make up differentiated citizenship.